Predictors of Mortality in Adults with Human Immunodeficiency Virus-Associated Tuberculous Meningitis: A Systematic Review and Meta-Analysis - Ellen Ferlita Tirtana; Ni Made Susilawathi; Anak Agung Raka Sudewi (Sriwijaya Journal of Neurology, 2026)
Background: Tuberculous meningitis (TBM) is the most lethal form of tuberculosis, and human immunodeficiency virus (HIV) co-infection is its single most important risk factor. The magnitude of mortality specific to HIV-associated TBM, and the factors that predict death, have not been synthesised quantitatively. Objective: To estimate the pooled all-cause mortality of adults with HIV-associated TBM and to identify its determinants. Methods: PubMed/MEDLINE and Europe PMC were systematically searched for cohort studies and randomised controlled trials reporting mortality in adults with HIV-associated TBM; this was a two-database, single-reviewer review with full-text verification. All-cause mortality was pooled as a proportion (random-effects, DerSimonian-Laird, logit transformation); adjusted ratio measures for one predictor domain reported by at least three studies were pooled on the log scale. Certainty was rated with GRADE. Results: Twelve studies (3,442 adults, 1,303 deaths) were included. In clinically ascertained cohorts and trials (k=11) pooled mortality was 47.0% (95% CI 41.4–52.7; I²=83.9%); the exploratory all-study estimate was 44.2% (95% CI 34.5–54.4; I²=96.4%; prediction interval 14.0–79.4%), heterogeneity being explained almost entirely by one national-registry cohort (17.3%). Advanced MRC/BMRC disease grade was the strongest predictor of death (pooled adjusted ratio 4.15, 95% CI 3.19–5.41; I²=0%). Mortality did not decline over the study period, and no small-study effect was detected. Conclusion: Approximately one in two adults with HIV-associated TBM died, without improvement despite expanding antiretroviral access, although the wide prediction interval and very low certainty demand caution. Advanced disease grade at presentation was the dominant predictor, underscoring the value of earlier diagnosis.